Metal Finds and Coins - Lichtenberger, Achim; Raja, Rubina (Brepols, 2020)
The Decapolis city of Jerash has long attracted attention from both travellers and scholars, due both to the longevity of the site, and the remarkable finds uncovered during successive phases of excavation that have taken place from 1902 onwards. Between 2011 and 2016, a Danish-German team, led by the universities of Aarhus and Münster, focused their attention on the Northwest Quarter of Jerash - the highest point within the walled city - and this volume is the second in a series of books presenting the team’s final results. This volume offers an in-depth analysis of the coins and metal remains found in Jerash during the excavations. The contributions gathered here cover the small metal finds from the Northwest Quarter, as well as examining Greek, Roman, Byzantine, and Islamic coins.